Designing and validating a new Asian family scale - Musa, Ramli; Md. Aris, Mohd. Aznan; Draman, Samsul; Abdullah, Kartini; Bujang, M.A (The Faculty of Medicine, International Islamic University Malaysia, 2015)
Introduction: All available family scales are designed for western countries and there is no validated family scale which is specifically devised for Asian population. The difference in culture and family values warrants the formulation of a specific Asian family scale to cater the regional needs. The objectives are to devise and validate a new family scale and eventually to validate it for Malaysian population. Method: The development of the questionnaire can be divided into 5 stages; identifying the domains of Asian family values, items identification for each domain and language review, pretest the pre-final version, pilot study and validation. Respondents were recruited from different ethnic groups and cultural backgrounds to represent the Malaysian population. They were selected by using stratified quota sampling from various health centres in the district of Kuantan, Malaysia. Results: A total of 588 participants enrolled in the validation stage with various ethnic backgrounds. Bartlet’s KMO value is 0.93. From 43 items, 67% had good factor loading (>0.4) and 13 items were finally dropped. Total Cronbach’s alpha values of 0.9 with 5 domains were identified by using exploratory factor analysis. There are 6 items in each domain. Conclusion: This new scale has good psychometric properties and it is a valid family scale for Malaysians. Further psychometric evaluation will further enhance the evidence for other populations in Asia.